Dithiolene Complexes of First‐Row Transition Metals for Symmetric Nonaqueous Redox Flow Batteries. Issue 19 (3rd September 2019) - Hogue, Ross W.; Armstrong, Craig G.; Toghill, Kathryn E.
Abstract: Five metal complexes of the dithiolene ligand maleonitriledithiolate (mnt 2− ) with M=V, Fe, Co, Ni, Cu were studied as redox‐active materials for nonaqueous redox flow batteries (RFBs). All five complexes exhibit at least two redox processes, making them applicable to symmetric RFBs as single‐species electrolytes, that is, as both negolyte and posolyte. Charge–discharge cycling in a small‐scale RFB gave modest performances for [(tea)2 Vmnt ], [(tea)2 Comnt ], and [(tea)2 Cumnt ] whereas [(tea)Femnt ] and [(tea)2 Nimnt ] (tea=tetraethylammonium) failed to hold any significant capacity, indicating poor stability. Independent negolyte‐ and posolyte‐only battery cycling of a single redox couple, as well as UV/Vis spectroscopy, showed that for [(tea)2 Vmnt ] the negolyte is stable whereas the posolyte is unstable over multiple charge–discharge cycles; for [(tea)2 Comnt ], [(tea)2 Nimnt ], and [(tea)2 Cumnt ], the negolyte suffers rapid capacity fading although the posolyte is more robust. Identifying a means to stabilize Vmnt 3−/2− as a negolyte, and Comnt 2−/1−, Nimnt 2−/1−, and Cumnt 2−/1− as posolytes could lead to their use in asymmetric RFBs. Abstract : Both positive and negative : Symmetric nonaqueous redox flow batteries employing metal–dithiolene complexes as the redox‐active species in both the negative and positive half‐cells are demonstrated with five metal complexes of the dithiolene ligand maleonitriledithiolate (mnt 2− ) with M=V, Fe, Co, Ni, Cu. All five complexes exhibit at least two redox processes, making them applicable to symmetric RFBs as single‐species electrolytes, that is, as both negolyte and posolyte.